AB0761 Efficacy of per-Cutaneous Ultrasound Guided Drainage of Degenerative Meniscal Cysts in Knee Osteoarthritis Patients. (15th July 2016) - Mortada, M.; Ezzeldin, N.; Hammad, M.
Abstract : Background: Meniscal cysts presented in about 4% of patients with knee osteoarthritis [1]. Meniscal cysts may result in pain and disability in the knee. Ultrasound may be used for therapeutic aspiration of the cyst [2]. Objectives: To evaluate the efficacy of ultrasound guided percutaneous drainage of symptomatic meniscal cysts in patients with knee osteoarthritis. Methods: Ultrasound guided percutaneous drainage of symptomatic meniscal cysts were performed in 38 patients with Knee osteoarthritis in the period between January 2013 and December 2015. Thirty cysts were related to the medial meniscus and 8 cysts were related to the lateral meniscus. Cysts were injected with local anaesthetic before completion of procedure. All 38 patients were subsequently followed up one month and 6 months after the aspiration with the primary outcome measures were the Western Ontario and McMaster Universities OA Index total pain score WOMAC (a Likert scale), patient global assessment (PGA) questionnaires and musculoskeletal ultrasonography assessment. Results: In every case the procedure was well tolerated. Complete aspiration of the cyst were performed in 15 patients (39.5%) and partial aspiration were performed in 23 patients (60.5%). Before aspiration US meniscal cyst measurements 29.5±9.2 mm * 13.6±4.5 mm. At the end of the 1st month, there was a reduction of 50% in the WOMAC pain score. 89.4% (34 patients) felt that their knee pain had improved compared to baseline. At this time point just US meniscal cyst measurements 19.5±5.2 mm * 11.6±4.1 mm. At the end of the 6th month post aspiration, there was a reduction in the WOMAC pain score of 30%. At this time point just 78.9% (30 patients) felt that their knee pain had improved compared to baseline. At this time point just US meniscal cyst measurements 25.5±6.2 mm * 13.6±3.6 mm. Patient outcomes did not significantly correlate with any meniscal cyst characteristic. Complete aspiration was associated with better outcomes. Conclusions: Ultrasound-guided percutaneous aspiration of degenerative meniscal cysts is a well-tolerated, simple, and safe procedure for patients with knee osteoarthritis. References: Campbell SE, Sanders TG, Morrison WB. MR imaging of meniscal cysts: incidence, location, and clinical significance. AJR Am J Roentgenol. 2001;177 (2): 409–13. P. J. MacMahon, D. D. Brennan, D. Duke, S. Forde, and S. J. Eustace, "Ultrasound-guided percutaneous drainage of meniscal cysts: preliminary clinical experience, " Clinical Radiology, vol. 62, no. 7, pp. 683–687, 2007. Disclosure of Interest: None declared